Analisis Kemampuan Penalaran Matematis Siswa dalam Menyelesaikan Soal Cerita dan Kaitannya dengan Hasil Belajar Kelas XI MIPA G SMAN 2 Kota Bengkulu - Aqiela Mardhatillah; Haji, Saleh (Jurnal Padegogik, 2024)
This research aims to describe the level of mathematical ability that students have, especially in terms of reasoning. The students' reasoning ability was tested through story-based problems, as well as explaining its correlation with learning outcomes. This research uses a qualitative descriptive strategy that focuses on 10 students of class XI majoring in Mathematics and Natural Sciences at SMA Negeri 2 Bengkulu City. The data obtained in this study were obtained through observation, documentation, and conducting written tests on the students who were the focus of this study. The written test given amounted to 5 items of description questions guided by mathematical reasoning indicators. The data obtained from observations and written tests were analyzed through analytical steps, namely data selection, presentation, and finally drawing conclusions based on the data obtained. The results of the analysis show that there are 20% of students who have high, or low mathematical reasoning ability, so the remaining 60% are students with moderate mathematical reasoning ability. If correlated with student learning outcomes with an average of 44, then the reasoning ability of students at SMA 2 Bengkulu City is in the medium category.